1995
DOI: 10.1002/mus.880180405
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic sudomotor function and aging

Abstract: Many studies have reported the influence of aging on different portions of the autonomic nervous system components but only partially for the sympathetic cholinergic system. We evaluated postganglionic sudomotor function in 196 healthy subjects, 104 women and 92 men, by determining sweat gland density (SGD) per square centimeter of skin, on the dorsum of the hand and foot, with the impression mold technique. The age range was from 5 to 84 years. A significant decrease of SGD was observed in both hand and foot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…They found that sweating volume on QSARTis greater in menand progressively declines with age at lower extremity sites. Also, there is a report that the density of sweating glands was decreased with aging (20). In this study, all subjects aged under 65 years old were recruited and there was no significant difference in age or sex between non-diabetic controls and diabetic patients (Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…They found that sweating volume on QSARTis greater in menand progressively declines with age at lower extremity sites. Also, there is a report that the density of sweating glands was decreased with aging (20). In this study, all subjects aged under 65 years old were recruited and there was no significant difference in age or sex between non-diabetic controls and diabetic patients (Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…With advancing age in both rodents and humans, exteroception and proprioception become impaired (Foster et al, 1976;Macintosh and Sinclair, 1978;Kenney and Fowler, 1988;Schmidt et al, 1990;Ferrell et al, 1992;AbdelRahman and Cowen, 1993;de Neeling et al, 1994;Gescheider et al, 1994;Ferrer et al, 1995;Quoniam et al, 1995;Robbins et al, 1995). Peripheral nerves of aged animals show both loss of fibers and degenerative changes (Cowen et al, 1982;Dhall et al, 1986;Mione et al, 1988;Cowen and Thrasivoulou, 1990;Navarro and Kennedy, 1990;Abdel-Rahman and Cowen, 1993).…”
Section: Sensory Impairments and Selective Vulnerability During Agingmentioning
confidence: 96%
“…Sweat drops imprint in the silastic material and quantification is determined by measuring the number of activated sweat glands per square centimetre. Sensitivity of the silastic method has not been evaluated [75,76].…”
Section: Other Tests Of Sudomotor Functionmentioning
confidence: 99%